2020
DOI: 10.1002/anie.202005554
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Reconstitution Reveals a Central Role for the N‐Oxygenase PvfB in (Dihydro)pyrazine‐N‐oxide and Valdiazen Biosynthesis

Abstract: The Pseudomonas virulence factor (pvf) operon is essential for the biosynthesis of two very different natural product scaffolds: the (dihydro)pyrazine-N-oxides and the diazeniumdiolate, valdiazen. PvfB is a member of the nonheme diiron N-oxygenase enzyme family that commonly convert anilines to their nitroaromatic counterparts. In contrast, we show that PvfB catalyzes N-oxygenation of the aamine of valine, first to the hydroxylamine and then the nitroso, while linked to the carrier protein of PvfC. PvfB modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…57 A comproportionation reaction between NO 2 − and a hydroxyamino group has been proposed to form the diazeniumdiolate moiety. 57,58 Referring to the two proposed transient intermediates involved in cremeomycin (7) biosynthesis, we suggest that the NO x -mediated nonenzymatic mechanism is also applicable to nitrogen−nitrogen bond formation in alanosine (6), fragin, and valdiazen biosynthesis.…”
mentioning
confidence: 86%
“…57 A comproportionation reaction between NO 2 − and a hydroxyamino group has been proposed to form the diazeniumdiolate moiety. 57,58 Referring to the two proposed transient intermediates involved in cremeomycin (7) biosynthesis, we suggest that the NO x -mediated nonenzymatic mechanism is also applicable to nitrogen−nitrogen bond formation in alanosine (6), fragin, and valdiazen biosynthesis.…”
mentioning
confidence: 86%
“…Based on the homology observed among ham operons, it was suggested that members of the genera Pseudomonas , Pandorea, and Burkholderia may use the diffusible signal molecule—valdiazen (valinol diazeniumdiolate), which autoregulates its own biosynthesis and also of fragin. Fragin is a metallophore and its metal chelating ability is responsible for its antifungal property [ 184 , 185 , 186 ].…”
Section: Other Potential Qs Signalsmentioning
confidence: 99%
“…[11] Mechanistically, the T domain delivers the acyl thioester to the R domain for reduction by NADPH to give an aldehyde product. For example, Lys2 can reduce α-aminoadipate at C-6 to the semialdehyde in the biosynthesis of lysine in Saccharomyces cerevisiae; [12] CmlP is involved in the biosynthesis of the antibiotic chloramphenicol (Scheme 1) in Streptomyces; [13] PvfC is responsible for the synthesis of a family of pyrazine N-oxides in Pseudomonas virulence; [14,15] and HamD is related to valdiazen biosynthesis in Burkholderia cenocepacia (Scheme 1). [16] CARs have also recently attracted interest as green biocatalysts due to their abilities to convert a broad range of carboxylic acid substrates to the corresponding aldehydes.…”
Section: Introductionmentioning
confidence: 99%